Unraveling the structure of DNA during overstretching by using multicolor, single-molecule fluorescence imaging - van Mameren, Joost; Gross, Peter; Farge, Geraldine; Hooijman, Pleuni; Modesti, Mauro; Falkenberg, Maria; Wuite, Gijs J L; Peterman, Erwin J G (Proceedings of the National Academy of Sciences - PNAS, 2009)
Single-molecule manipulation studies have revealed that double-stranded DNA undergoes a structural transition when subjected to tension. At forces that depend on the attachment geometry of the DNA (65 pN or 110 pN), it elongates approximately 1.7-fold and its elastic properties change dramatically. The nature of this overstretched DNA has been under debate. In one model, the DNA cooperatively unwinds, while base pairing remains intact. In a competing model, the hydrogen bonds between base pairs break and two single DNA strands are formed, comparable to thermal DNA melting. Here, we resolve the structural basis of DNA overstretching using a combination of fluorescence microscopy, optical tweezers, and microfluidics. In DNA molecules undergoing the transition, we visualize double- and single-stranded segments using specific fluorescent labels. Our data directly demonstrate that overstretching comprises a gradual conversion from double-stranded to single-stranded DNA, irrespective of the attachment geometry. We found that these conversions favorably initiate from nicks or free DNA ends. These discontinuities in the phosphodiester backbone serve as energetically favorable nucleation points for melting. When both DNA strands are intact and no nicks or free ends are present, the overstretching force increases from 65 to 110 pN and melting initiates throughout the molecule, comparable to thermal melting. These results provide unique insights in the thermodynamics of DNA and DNA-protein interactions.